Symmetry and the standard model mathematics and particle physics - Robinson, Matthew B.; SpringerLink (Online service). (New York Springer, 2011)
While elementary particle physics is an extraordinarily fascinating field, the huge amount of knowledge necessary to perform cutting-edge research poses a formidable challenge for students. The leap from the material contained in the standard graduate course sequence to the frontiers of M-theory, for example, is tremendous. To make substantial contributions to the field, students must first confront a long reading list of texts on quantum field theory, general relativity, gauge theory, particle interactions, conformal field theory, and string theory. Moreover, waves of new mathematics are required at each stage, spanning a broad set of topics including algebra, geometry, topology, and analysis. Symmetry and the Standard Model: Mathematics and Particle Physics, by Matthew Robinson, is the first volume of a series intended to teach math in a way that is catered to physicists. Following a brief review of classical physics at the undergraduate level and a preview of particle physics from an experimentalist's perspective, the text systematically lays the mathematical groundwork for an algebraic understanding of the Standard Model of Particle Physics. It then concludes with an overview of the extensions of the previous ideas to physics beyond the Standard Model. The text is geared toward advanced undergraduate students and first-year graduate students.
Review of Classical Physics -- A Preview of Particle Physics -- Algebraic Foundations -- First Principles and the Standard Model -- Beyond the Standard Model of Particle Physics.
Keywords: Standard model (Nuclear physics) -- Mathematics; Particles (Nuclear physics) -- Mathematics; Group theory; Lie groups; Quantum field theory -- Mathematics; Electronic books